Wali Songo Festival: Tracking Islamic Heritage and Building Islamic Brotherhood - Ropi, Ismatu (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
26 June to 25 July 1999 is of special significance for Indonesian Muslim. Located in Surabaya, East Java, the Wali Songo Festival, the greatest Islamic festival of the year, was held by the Muslim during that time. The Festival -which was officially opened by B.J. Habibie, then the President of Indonesia-was aimed as an important media for the expression of Indonesian Islamic culture and civilization. Thus the festival provided the visitors with the exhibition of many aspects of Islamic civilization achieved by the Indonesian Muslim, from archeological materials - such as the duplicated sword of the Prophet Muhammad, the gravestone of Sunan Ampel and Sunan Bonang (two of the nine Islamic preachers in Indonesia, Wali Songo - to the intellectual heritage like the decorated Qur'ân in various forms and the Islamic books by the 'ulâmi' (Kitab Kuning). In addition, the festival also exhibited many products by the Muslim, such as calligraphy, rosaries (tasbih), and turbans (peci).DOI: 10.15408/sdi.v6i3.728